First subtract the constant to the other side to simplify it for now
y-5=-x^2+6x
Then pull out a common factor so the coefficient is x^2
y-5=-1(x^2-6x)
Next you take 1/2 of the b value (-6) and square it to find your c value
[1/2(-6)]^2=9
After that plug 9 into your equation as your c value
y-5=-1(x^2-6x+9)
Adding the C-value (9) causes the equations to become unbalanced so you need to balance them back out by minus 9 to the other side
y-14=-1(x^2-6x+9)
Now you want to simplify the equation on the right side.
y-14=-1(x-3)^2
Finally you want to add the constant back to the right side.
y=-1(x-3)^2+14 <——— vertex form
maximum=(3,14)